The dilemma of extensive sheep production systems in highlands of the semiarid northwest of Tunisia - M. Rekik; M. Mahouachi; M. Gharbi; W. Attia; L. Medhioub (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2000)
To characterize extensive sheep production systems in the semiarid bioclimate of Northwest Tunisia, two mountain sites were selected. The production systems were sedentary and in close relationship with cereal production. Barley, along with the practice of fallowing on low-fertility sloping lands, had replaced rangelands. The flocks were usually small and increasingly confined to smaller spaces. They were dependent on poorly efficient feed strategies and characterized by low technical-economical performances. In addition, farmers’ financial support of their flocks was precarious and the farmers themselves depended on climatic and economical changes. Faced with the space extension and small flock size problems, it seems necessary to increase sheep productivity in these areas. Recommendations that take into account the particular geographical, technical and economical context of the farms are proposed.